The invention discloses a nickel-based single crystal alloy gamma apos based on coarsening kinetics. Phase evaluation method

By processing the air membrane pores on the nickel-based single crystal alloy and performing aging test, and fitting the new roughening kinetic equation with the roughening kinetic equation, the problem of inaccurate evaluation of the γ' phase size and roughening activation energy of nickel-based single crystal alloy in the prior art was solved, and the accurate evaluation of the γ' phase roughening law and activation energy law of the γ' phase was achieved, and the efficiency of alloy structure stability analysis was improved.

CN119534518APending Publication Date: 2025-02-28SHAANXI UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411744153.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, statistical evaluation of the γ' phase size and coarse activation energy of the microstructure of nickel-based single crystal alloys is not accurate enough.

Method used

Using a roughening kinetic evaluation method, aging test was performed by processing preset angle air film pores on the initial sample of nickel-based single crystal alloy, aging test was performed, the microstructure morphology of the γ' phase was obtained, the average size data of the γ' phase was counted, and the new roughening kinetic equation was fitted with the roughening kinetic equation to evaluate the roughening law and activation energy law of the γ' phase size.

Benefits of technology

The accurate evaluation of the γ' phase size and coarse activation energy of nickel-based single crystal alloy is achieved, and the coarseness and activation energy of the γ' phase can be predicted more accurately, improving the efficiency of evaluating the alloy structure stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534518A_ABST
    Figure CN119534518A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy stability analysis, and relates to a nickel-based single crystal alloy gamma'phase evaluation method based on coarsening kinetics. According to the method, the air film hole with the preset angle is machined in the initial sample of the nickel-based single crystal alloy. Carrying out aging tests of different preset times on the nickel-based single crystal alloy sample after the air film holes are processed at a preset temperature; preparing a metallographic sample according to the initial sample after the aging test; the microstructure morphology of the gamma'phase of the metallographic sample is obtained; according to the microstructure morphology, carrying out statistics on gamma'phase average size data of a gamma 'phase in the metallographic specimen under different preset angles and different aging time conditions; and fitting a new coarsening kinetic equation and a gamma'phase strengthening coarsening activation energy formula containing the gas film hole with the angle, evaluating the size of the gamma 'phase by using the new coarsening kinetic equation, and evaluating a gamma' phase activation energy rule by using the gamma 'phase strengthening coarsening activation energy formula containing the gas film hole with the angle. And accurate evaluation of the nickel-based single crystal alloy gamma'phase size and the coarsening activation energy is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy stability analysis and relates to an evaluation method for a γ' phase of a nickel-based single crystal alloy based on coarsening kinetics. Background Art

[0002] Nickel-based single crystal superalloys have attracted much attention due to their excellent high-temperature performance. They are the preferred materials for manufacturing advanced aero-engine and gas turbine blades. They have the advantages of high high-temperature strength, stable organization and good casting process performance. Thrust-to-weight ratio is an important indicator of aero-engine performance, and increasing the turbine inlet temperature is one of the main ways to improve the thrust-to-weight ratio. However, the current development of nickel-based single crystal superalloys is not enough to fully meet the demand for higher turbine inlet temperatures. Therefore, the key improvement lies in efficient turbine blade cooling technology, and film cooling, one of the important cooling methods, can ensure the reliable operation of the engine. The microstructure of nickel-based single crystal alloys is mainly characterized by γ matrix and γ' strengthening phase. Under high-temperature service conditions, the size and distribution of γ' phase directly affect the creep performance, oxidation resistance and overall service life of the material. However, complex service environments can cause changes such as coarsening or dissolution of the γ' phase, weakening the high-temperature performance of the alloy. In addition, in order to improve the heat dissipation performance of turbine blades, film cooling technology is often used, and the processing of film holes will affect the organizational evolution and micromechanical properties of the blades. In actual work, turbine blades operate in complex high-temperature environments, and the changes in their microstructure morphology and the coarsening behavior of the γ' phase become key factors affecting the performance and life of the blades. Therefore, the accurate evaluation of the size coarsening law of the γ' phase in nickel-based single crystal alloys is of great significance and can provide a reliable theoretical basis for optimizing turbine blade material design and predicting service behavior.

[0003] In the prior art, the γ' phase size of the microstructure of nickel-based single crystal alloys is usually statistically evaluated through microscopic morphology observation and coarsening kinetics, and the coarsening activation energy is used to describe the energy threshold of the γ' phase coarsening behavior, but both have the problem of inaccurate evaluation. Summary of the invention

[0004] The purpose of the present invention is to provide a method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics, so as to solve the technical problem that the statistical evaluation of the γ' phase size and coarsening activation energy of the microstructure of the nickel-based single crystal alloy in the prior art is not accurate enough. The present invention can realize the accurate evaluation of the γ' phase size and coarsening activation energy of the nickel-based single crystal alloy.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics, comprising the following steps: Air film holes with a preset angle are machined on an initial sample of a nickel-based single crystal alloy; The nickel-based single crystal alloy sample after processing the air film hole is subjected to aging test at a preset temperature and for different preset times; Metallographic specimens were prepared based on the initial specimens after the aging test; Obtain the microstructure morphology of the γ' phase of the metallographic sample; According to the microstructure morphology, the average size data of the γ' phase in the metallographic sample under different preset angles and different aging time conditions are counted; Combining the coarsening kinetic equation with the average size data of the γ' phase, a new coarsening kinetic equation was fitted and established, and the coarsening law of the γ' phase size was evaluated using the new coarsening kinetic equation. According to the activation energy formula of γ' phase enhancement coarsening, the preset angle of air film pores and the preset temperature, the activation energy formula of γ' phase enhancement coarsening with air film pore setting angle was constructed, and the activation energy law of γ' phase was evaluated using the activation energy formula of γ' phase enhancement coarsening with air film pore setting angle.

[0006] Furthermore, the air film holes with a preset angle are processed on the initial sample of the nickel-based single crystal alloy as follows: The invention relates to machining air film holes on an initial sample of a nickel-based single crystal alloy by using an electric spark machining process.

[0007] Furthermore, the preset temperature is 950 degrees Celsius to 1100 degrees Celsius.

[0008] Furthermore, the preset time is 0 hours to 600 hours.

[0009] Furthermore, the metallographic sample is prepared according to the initial sample after the aging test, as follows: After the aging test, the plane of the initial sample is mechanically ground and polished, and then the surface of the polished initial sample is corroded by copper sulfate corrosive solution to obtain a metallographic sample.

[0010] Furthermore, the microstructure morphology of the γ' phase of the metallographic sample is obtained as follows: The metallographic samples were observed using a scanning electron microscope to obtain the microstructural morphology information of the alloy.

[0011] Furthermore, according to the microstructure morphology, the average size data of the γ' phase in the metallographic sample under different preset angles and different aging time conditions are statistically analyzed, as follows: The pixel information of SEM images is used to perform binary segmentation of the microstructure morphology of the reinforcement phase and the matrix phase; Perform contour recognition on the microstructure morphology after binary segmentation to extract the shape characteristics of the reinforcement phase; The size is measured according to the shape characteristics of the strengthening phase, and the size data under the conditions of aging experiments at different times and air film holes at different angles are counted; Get the average size based on the statistical size data.

[0012] Furthermore, the coarsening kinetic equation and the average size data of the γ' phase are combined to fit and establish a new coarsening kinetic equation, which is as follows: A new coarsening kinetic equation is constructed based on the average size data, the original coarsening kinetic equation, the coarsening rate index, the angular coarsening coefficient, the air film pore angle, the angle-affected coarsening rate index, the instantaneous angle influence coefficient, the instantaneous angle influence index and the time of the aging test.

[0013] Furthermore, the new roughening dynamic equation is as follows:

[0014] in, Cubic / rafted γ′ phase The average size of is the coarsening rate index, is the angle coarsening coefficient, is the air film hole angle, is the coarsening rate index affected by angle, is the instantaneous angle influence coefficient, is the instantaneous angle influence index, and are constants related to the material. The time for the aging test.

[0015] Furthermore, the activation energy formula for the γ' phase strengthening and coarsening is as follows:

[0016] in, is the activation energy of γ' phase coarsening, is a constant, is the instantaneous angle influence coefficient, is the air film hole angle, is the instantaneous angle influence index, is a constant related to the material, is the gas constant, is the preset temperature.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention processes air film holes with preset angles on the initial sample of nickel-based single crystal alloy, which is helpful to study the influence of different angles on the coarsening kinetics of the γ' phase and provides a basis for subsequent aging tests and metallographic analysis. The nickel-based single crystal alloy sample after processing the air film holes is subjected to aging tests at a preset temperature for different preset times; a metallographic sample is prepared based on the initial sample after the aging test, and a clear and accurate microstructure image can be obtained through appropriate cutting, grinding and polishing, etc., providing a basis for subsequent observation and measurement; the microstructure morphology of the γ' phase of the metallographic sample is obtained; according to the microstructure morphology, the average size data of the γ' phase in the metallographic sample under different preset angles and different aging time conditions is statistically analyzed, providing key data support for the fitting of the subsequent coarsening kinetic equation; combining the coarsening kinetic equation and the average size data of the γ' phase, a new coarsening kinetic equation is fitted and established, and the new coarsening kinetic equation is used to evaluate the coarsening law of the γ' phase size. By fitting the new coarsening kinetic equation, the coarsening law of the γ' phase size can be more accurately predicted and evaluated. According to the activation energy formula of γ' phase strengthening and coarsening, the preset angle of the air film hole and the preset temperature are used to construct the activation energy formula of γ' phase strengthening and coarsening with the air film hole setting angle, and the activation energy law of γ' phase is evaluated by using the activation energy formula of γ' phase strengthening and coarsening with the air film hole setting angle, which is convenient for quantitative evaluation of the activation energy law of γ' phase, helps to understand the difficulty of γ' phase coarsening under different conditions, and provides guidance for further design and optimization of alloys. The various steps of the present invention are interrelated and complementary, and together constitute a comprehensive evaluation system for the coarsening behavior of γ' phase of nickel-based single crystal alloy.

[0018] 2. The present invention mechanically grinds and polishes the plane of the initial sample after the aging test to remove the oxide layer, scratches and other unevenness on the surface of the sample after the aging test, so that the surface of the sample becomes smooth and flat, ensuring that a clear and interference-free image can be obtained when observed under a scanning electron microscope. The surface of the polished initial sample is then corroded by a copper sulfate corrosive solution, thereby forming a clear phase boundary on the surface of the sample to obtain a metallographic sample.

[0019] 3. The present invention uses the pixel information of the SEM image to perform binary segmentation on the microstructure morphology of the reinforcement phase and the matrix. Through the binary segmentation, the image information is simplified, and the efficiency and accuracy of subsequent processing are improved. The microstructure morphology after binary segmentation is contour recognized, and the shape characteristics of the reinforcement phase are extracted. Through contour recognition, the specific shape information of the reinforcement phase is obtained, providing accurate data support for size measurement. The size measurement is performed according to the shape characteristics of the reinforcement phase, and the size data of aging experiments at different times and air film hole conditions at different angles are statistically analyzed. Through size measurement and statistics, the size distribution and change trend of the γ' phase under different conditions are obtained, providing data support for the subsequent coarsening kinetic equation fitting; the average size is obtained based on the statistical size data, and the data representation is simplified to facilitate subsequent analysis and comparison. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a method flow chart of an embodiment of the present invention.

[0021] Figure 2 is a schematic diagram of the three-dimensional structure of the sample of the present invention, wherein: is the air film hole angle, for The complementary angle of Figure 3 is a cross-sectional view of a sample of the present invention, where D is the diameter of the air film hole; Figure 4 is a top view of a sample of the present invention; Figure 5 It is a γ' phase size identification diagram of the present invention, wherein a is a schematic diagram of a γ' strengthening phase of a nickel-based single crystal, and b is a γ' strengthening phase identification diagram of a nickel-based single crystal; Figure 6 is a graph showing the relationship between the size of the γ' phase at different angles and time of the present invention; Figure 7 is the angle coefficient fitting diagram; Figure 8 is the initial size diagram of the γ' phase at different angles; Fig. 9 It is a three-dimensional diagram of the angle and average size of the γ′ phase of the present invention; Fig.10 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0024] The present invention is further described in detail below in conjunction with the accompanying drawings: See also Fig.10 The present invention discloses a method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics, comprising the following steps: S1, machining air film holes with preset angles on the initial specimens of nickel-based single crystal alloys is helpful to study the effect of different angles on the coarsening kinetics of the γ' phase and provides a basis for subsequent aging tests and metallographic analysis.

[0025] S2, performing aging tests on the nickel-based single crystal alloy specimen after processing the air film hole at a preset temperature and for different preset times; S3, metallographic specimens are prepared according to the initial specimens after aging test. Through appropriate cutting, grinding and polishing, clear and accurate microstructure images can be obtained, providing a basis for subsequent observation and measurement; S4, obtain the microstructure morphology of the γ' phase of the metallographic sample, which provides a direct basis for the subsequent data statistics and the fitting of the coarsening kinetic equation; S5, according to the microstructure morphology, statistically analyzing the average size data of the γ' phase in the metallographic sample under different preset angles and different aging time conditions, so as to provide key data support for the fitting of the subsequent coarsening kinetic equation; S6, combining the coarsening kinetic equation and the average size data of the γ' phase, fitting and establishing a new coarsening kinetic equation, and using the new coarsening kinetic equation to evaluate the coarsening law of the γ' phase size. By fitting the new coarsening kinetic equation, the coarsening law of the γ' phase size can be predicted and evaluated more accurately.

[0026] S7, constructing a γ' phase enhancement coarsening activation energy formula according to the coarsening activation energy formula, the preset angle of the air film pores and the preset temperature, and using the γ' phase enhancement coarsening activation energy formula to evaluate the γ' phase activation energy law.

[0027] The present invention not only helps to deeply understand the coarsening mechanism of the γ' phase through the newly constructed coarsening kinetic equation and the γ' phase enhanced coarsening activation energy formula, but also provides a scientific basis for the design and optimization of materials.

[0028] Embodiment 1: See also Fig.10 This embodiment discloses a method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics, comprising the following steps: S1, a gas film hole with a preset angle is machined on the initial sample of the nickel-based single crystal alloy, see Figure 2 , Figure 3 and Figure 4 ; Preferably, the initial sample of the nickel-based single crystal alloy is a block structure initial sample obtained by wire cutting of the nickel-based single crystal alloy.

[0029] Preferably, the air film holes with a preset angle are processed on the initial sample of the nickel-based single crystal alloy, specifically as follows: Using an electric spark machining process, the gas film holes are machined on the initial sample of the nickel-based single crystal alloy; The angle of the air film hole is 30 degrees.

[0030] S2, performing aging tests on the nickel-based single crystal alloy specimen after processing the air film hole at a preset temperature and for different preset times; Preferably, the preset temperature is 950 degrees Celsius.

[0031] Preferably, the preset time is 1 hour.

[0032] S3, prepare the metallographic sample according to the initial sample after the aging test, as follows: After the aging test, the plane of the initial sample is mechanically ground and polished to remove the oxide layer, scratches and other unevenness on the surface of the sample after the aging test, so that the surface of the sample becomes smooth and flat, ensuring that a clear and interference-free image can be obtained when observed under a scanning electron microscope. The surface of the polished initial sample is then corroded by copper sulfate etching solution to form a clear phase boundary on the surface of the sample to obtain a metallographic sample. This corrosion effect makes it easier to identify and measure the size, shape and distribution of the γ' phase under a scanning electron microscope.

[0033] S4, obtain the microstructure morphology of the γ' phase of the metallographic sample, as follows: The metallographic samples were observed using a scanning electron microscope to obtain the microstructural morphology information of the alloy.

[0034] S5, according to the microstructure morphology, the average size data of the γ' phase in the metallographic sample under different preset angles and different aging time conditions are statistically analyzed, as follows: The pixel information of the SEM image is used to perform binary segmentation of the microstructure morphology of the reinforcement phase (black) and the matrix phase (white). In the image after binary segmentation, the reinforcement phase and the matrix phase are represented by black and white, respectively, which is helpful for subsequent shape recognition and size measurement. Through binary segmentation, the image information is simplified and the efficiency and accuracy of subsequent processing are improved.

[0035] The contour recognition is performed on the microstructure morphology after binary segmentation to extract the shape characteristics of the reinforcement phase. These shape characteristics include area, perimeter, major axis length, minor axis length, etc., which are the basis for subsequent size measurement. Through contour recognition, the specific shape information of the reinforcement phase is obtained to provide accurate data support for size measurement.

[0036] The size of the strengthening phase is measured according to its shape characteristics, and the size data of the aging experiments at different times and the air film holes at different angles are counted. Through size measurement and statistics, the size distribution and change trend of the γ' phase under different conditions are obtained, providing data support for the subsequent coarsening kinetic equation fitting; The average size is obtained based on the statistical size data, and the data representation is simplified to facilitate subsequent analysis and comparison.

[0037] S6, combining the coarsening kinetic equation and the average size data of the γ' phase, a new coarsening kinetic equation is fitted and established, and the coarsening law of the γ' phase size is evaluated using the new coarsening kinetic equation, as follows: A new coarsening kinetic equation is constructed based on the average size data, the original coarsening kinetic equation, the coarsening rate index, the angular coarsening coefficient, the air film pore angle, the angle-affected coarsening rate index, the instantaneous angle influence coefficient, the instantaneous angle influence index and the time of the aging test.

[0038] Preferably, the new roughening kinetic equation is as follows:

[0039] in, Cubic / rafted γ′ phase The average size of is the coarsening rate index, is the angle coarsening coefficient, is the air film hole angle, is the coarsening rate index affected by angle, is the instantaneous angle influence coefficient, is the instantaneous angle influence index, and are constants related to the material. The time for the aging test.

[0040] S7, constructing a γ' phase enhancement coarsening activation energy formula according to the coarsening activation energy formula, the preset angle of the air film pores and the preset temperature, and using the γ' phase enhancement coarsening activation energy formula to evaluate the γ' phase activation energy law.

[0041] Preferably, the activation energy formula for the γ' phase strengthening and coarsening is as follows:

[0042] in, is the activation energy of γ' phase coarsening, is a constant, is the instantaneous angle influence coefficient, is the air film hole angle, is the instantaneous angle influence index, is a constant related to the material, is the gas constant, is the preset temperature.

[0043] Embodiment 2: See also Fig.10 Based on the above embodiments, the difference between this embodiment and embodiment 1 is that the angle of the air film hole is 90 degrees.

[0044] The preset temperature of the aging test is 1125 degrees Celsius.

[0045] The preset time of the aging test is 300 hours.

[0046] Embodiment three: See also Fig.10 Based on the above embodiments, the difference between this embodiment and embodiment 1 is that the angle of the air film hole is 150 degrees.

[0047] The preset temperature of the aging test is 1100 degrees Celsius.

[0048] The preset time of the aging test is 600 hours.

[0049] Embodiment 4: See also Figure 1 This embodiment discloses a method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics, comprising the following steps: Step 1: Obtain an initial sample of a nickel-based single crystal alloy, and process an air film hole of a preset angle on the initial sample, as follows: Obtain an initial sample of a nickel-based single crystal alloy, and perform air film hole processing of a preset angle on the initial sample; perform wire cutting on the nickel-based single crystal alloy to obtain the initial sample, the initial sample may be a rectangular parallelepiped structure, a block structure with a length, width and height of 10 mm, 8 mm and 1.2 mm, or a block structure of other sizes, such as a block structure with a length, width and height of 8 mm, 5 mm and 2 mm. Use an electrospark machining process to machine air film holes of 30 degrees, 60 degrees, 90 degrees, 120 degrees and 150 degrees.

[0050] Step 2: The nickel-based single crystal alloy sample after processing the air film hole is subjected to an aging test at a preset temperature for different preset times, as follows: The nickel-based single crystal alloy sample is subjected to an aging test at a preset temperature for different preset times; the preset temperature may be 980 degrees Celsius or 1100 degrees Celsius, and in an exemplary embodiment of the present disclosure, the preset temperature is 980 degrees Celsius. The preset time is 100 hours, 200 hours, 400 hours, or 600 hours.

[0051] Step 3: Processing the initial sample after the aging test to prepare a metallographic sample; The initial sample after the aging test is processed to obtain a metallographic sample; the 10mm×8mm plane of the initial sample after the aging test is mechanically ground and polished, and then the surface of the polished initial sample is corroded by CuSO4 (copper sulfate) corrosive liquid to obtain a metallographic sample. When preparing the metallographic sample, only one surface of the initial sample can be processed, or multiple edges can be processed at the same time, or the entire initial sample can be mechanically ground and polished, and then the polished alloy surface can be corroded by CuSO4 (copper sulfate) corrosive liquid.

[0052] Step 4: Observe the metallographic sample by a microscopic analysis method to obtain the microstructure morphology of the γ' phase; The metallographic sample is observed to obtain the microstructure morphology of the metallographic sample; the metallographic sample is observed using a scanning electron microscope to obtain the microstructure morphology information of the alloy. Through microscopic analysis, the distribution and morphological characteristics of the γ' phase are clearly observed, and the size of the γ' phase and its coarsening law under different conditions are recorded and analyzed in detail.

[0053] Step 5: According to the microstructure morphology, the average size data of the γ' phase in the metallographic sample under different preset angles and different aging time conditions are counted; The average size of the γ' strengthening phase in the metallographic sample at different preset angles and different aging conditions is counted. The accurate measurement of the γ' phase size is achieved through the following three main steps: First, the pixel information of the SEM image is used to perform binary segmentation of the reinforcement phase (black) and the matrix phase (white); Then, contour recognition is performed to extract the shape features of the reinforcement phase; Finally, the size measurement is performed based on the identified contour information, so as to efficiently and accurately calculate the size data of the γ' phase under different angles and aging conditions, such as Figure 5 The average value was calculated to provide reliable data support for subsequent analysis.

[0054] Step 6: Combine the coarsening kinetic equation and the average size data of the γ' phase to fit and establish a new coarsening kinetic equation to evaluate the coarsening law of the γ' phase size, and fit and establish a new coarsening activation energy equation to evaluate the coarsening activation energy of the γ' phase. The details are as follows: A new coarsening kinetic equation is established according to the coarsening kinetic equation and the average size of the γ' phase; The original coarsening kinetic equation is: (1) Where: Cubic / rafted γ′ phase The average size of is the average size of the cubic / rafted γ′ phase before aging, for, is the time, and n is the coarsening rate index.

[0055] It is known that the size of the γ' phase of the gas film hole of nickel-based single crystal follows formula (1), and under the specific conditions of EDM gas film hole, the influence of the initial processing on its coarsening kinetic curve cannot be ignored. Therefore, considering the influence of the initial processing on the size of the γ' phase, the following correction is made to formula (1): (2) Where: is the coefficient of time, is a constant, is the coarsening rate index affected by time. Figure 6 This is a fitting curve of the γ′ phase size under different angle conditions. It can be seen from the figure that the change of the air film pore angle has a significant effect on the γ′ phase coarsening curve, indicating that different inclination angles will cause differences in the coarsening behavior of the γ′ phase. Further analysis found that the coarsening rate index at different angles are basically the same, indicating that the inclination angle has little effect on the coarsening rate index. and As the angle changes, it changes significantly, indicating and All about angle Therefore, formula (2) can be modified as follows: (3) Where: and for Function of . Then study and ,like Figure 7 , the coefficient of time in the fitting formula at different angles By fitting, we can get Function expression of different angle thickening formulas. The fitting result of is in the form of a parabola, so The expression of is shown in formula (4): (4) Where: is the instantaneous angle influence coefficient, is the instantaneous angle influence index, are all constants. And it can be found that when The experimental data can be fitted well.

[0056] Again From formula (3), we can know that When the γ′ phase coarsening size is ,like Figure 8 As shown, The γ′ phase size data at 2000 is fitted. It can be seen from the figure that The size of the γ′ phase also shows a parabolic trend. The expression of is shown in formula (5): (5) Where: is the coarsening rate index under the influence of angle, is the angle coarsening coefficient, is a constant.

[0057] when When , the experimental data can be well fitted. Therefore, we get The expression of , formula (3) can be rewritten as: (6) Where: Cubic / rafted γ′ phase The average size of is the coarsening rate index, is the angle coarsening coefficient, is the air film hole angle, is the coarsening rate index affected by angle, is the instantaneous angle influence coefficient, is the instantaneous angle influence index, and are constants related to the material. For the duration of the aging test, see Fig. 9 The three-dimensional diagram is fitted for the angle and average size of the γ′ phase of the present invention.

[0058] It is known that the activation energy of γ' phase reinforcement coarsening follows the following formula: (7) Where: is the activation energy of γ' phase reinforcement coarsening, is a constant, is the gas constant, is the preset temperature.

[0059] By adding the angle influence factor to the activation energy formula of γ' phase reinforcement coarsening, we can get: (8) Where: is the activation energy of γ' phase coarsening, is a constant, is the instantaneous angle influence coefficient, is the air film hole angle, is the instantaneous angle influence index, is a constant related to the material, is the gas constant, is the preset temperature.

[0060] The present invention effectively characterizes the coarsening law of the γ' phase size by introducing the air film hole angle influencing factor, and provides a scientific analysis basis for the subsequent study of the microstructure stability of nickel-based single crystal alloys under high temperature aging conditions, thereby improving the efficiency of evaluating the stability of alloy structures, and further ensuring the accuracy and precision in analyzing the performance and reliability of blade materials.

[0061] In summary, the beneficial effects of the present invention are as follows: The present invention can make more accurate analysis: by introducing the angle influencing factor, the coarsening kinetic equation can more accurately predict the size of the γ′ phase at different angles, and the coarsening activation energy equation can more accurately predict the coarsening activation energy of the γ′ phase at different angles. This accuracy can be controlled within 10%, which is more reliable than the existing technology.

[0062] The present invention improves the analysis efficiency: by establishing a new coarsening kinetic equation, the microstructure stability of nickel-based single crystal alloy under high temperature aging conditions can be more effectively analyzed. This provides a more reasonable analysis basis, thereby improving the efficiency of alloy stability analysis.

[0063] The present invention improves the accuracy of blade reliability analysis: This technology can help improve the accuracy of blade reliability analysis. Through in-depth research and prediction of the γ′ phase size coarsening law, the performance and life of the blade in a high temperature environment can be better evaluated.

[0064] The invention expands the knowledge field: the development of this technology expands the understanding of the coarsening kinetic equation and introduces the angle influence factor into the prediction of the γ′ phase size and the coarsening activation energy. This method can provide new ideas and methods for research in related fields.

[0065] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics, characterized in that: The following steps are involved: Air film holes with a preset angle are machined on an initial sample of a nickel-based single crystal alloy; The nickel-based single crystal alloy sample after processing the air film hole is subjected to aging test at a preset temperature and for different preset times; Metallographic specimens were prepared based on the initial specimens after the aging test; Obtain the microstructure morphology of the γ' phase of the metallographic sample; According to the microstructure morphology, the average size data of the γ' phase in the metallographic sample under different preset angles and different aging time conditions are counted; Combining the coarsening kinetic equation with the average size data of the γ' phase, a new coarsening kinetic equation was fitted and established, and the coarsening law of the γ' phase size was evaluated using the new coarsening kinetic equation. According to the activation energy formula of γ' phase enhancement coarsening, the preset angle of air film pores and the preset temperature, the activation energy formula of γ' phase enhancement coarsening with air film pore setting angle was constructed, and the activation energy law of γ' phase was evaluated using the activation energy formula of γ' phase enhancement coarsening with air film pore setting angle.

2. The method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics according to claim 1, characterized in that: The method of machining a gas film hole with a preset angle on the initial sample of the nickel-based single crystal alloy is as follows: The invention relates to machining air film holes on an initial sample of a nickel-based single crystal alloy by using an electric spark machining process.

3. The method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics according to claim 1, characterized in that: The preset temperature is 950 degrees Celsius to 1100 degrees Celsius.

4. The method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics according to claim 1, characterized in that: The preset time is from 0 hours to 600 hours.

5. The method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics according to claim 1, characterized in that: The metallographic sample is prepared according to the initial sample after the aging test, as follows: After the aging test, the plane of the initial sample is mechanically ground and polished, and then the surface of the polished initial sample is corroded by copper sulfate corrosive solution to obtain a metallographic sample.

6. The method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics according to claim 1, characterized in that: The microstructure morphology of the γ' phase of the metallographic sample is obtained as follows: The metallographic samples were observed using a scanning electron microscope to obtain the microstructural morphology information of the alloy.

7. The method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics according to claim 1, characterized in that: According to the microstructure morphology, the average size data of the γ' phase in the metallographic sample under different preset angles and different aging time conditions are statistically analyzed, as follows: The pixel information of SEM images is used to perform binary segmentation of the microstructure morphology of the reinforcement phase and the matrix phase; Perform contour recognition on the microstructure morphology after binary segmentation to extract the shape characteristics of the reinforcement phase; The size is measured according to the shape characteristics of the strengthening phase, and the size data under the conditions of aging experiments at different times and air film holes at different angles are counted; Get the average size based on the statistical size data.

8. The method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics according to claim 1, characterized in that: The coarsening kinetic equation and the average size data of the γ' phase are combined to fit and establish a new coarsening kinetic equation, which is as follows: A new coarsening kinetic equation is constructed based on the average size data, the original coarsening kinetic equation, the coarsening rate index, the angular coarsening coefficient, the air film pore angle, the angle-affected coarsening rate index, the instantaneous angle influence coefficient, the instantaneous angle influence index and the time of the aging test.

9. The method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics according to claim 8, characterized in that: The new roughened dynamic equation is as follows: in, Cubic / rafted γ′ phase The average size of is the coarsening rate index, is the angle coarsening coefficient, is the air film hole angle, is the coarsening rate index affected by angle, is the instantaneous angle influence coefficient, is the instantaneous angle influence index, and are constants related to the material. The time for the aging test.

10. The method for evaluating the γ' phase of a nickel-based single crystal alloy based on coarsening kinetics according to claim 1, characterized in that: The activation energy formula for the γ' phase strengthening and coarsening is as follows: in, is the activation energy of γ' phase coarsening, is a constant, is the instantaneous angle influence coefficient, is the air film hole angle, is the instantaneous angle influence index, is a constant related to the material, is the gas constant, is the preset temperature.

Citation Information

Patent Citations

  • Method of evaluating high-temperature long-term aging strengthening phase coarsening rule of nickel-based single crystal alloy

    CN110196262A

  • Single crystal alloy raft quantitative characterization method based on digital image algorithm

    CN111738130A

  • Prediction method for gamma'-phase evolution of multi-component nickel-based superalloy based on data driving

    CN112185488A

  • Method for rapidly characterizing and analyzing microstructure evolution of nickel-based single crystal high-temperature alloy

    CN113376015A

  • Digital processing method for thermal deformation microstructure of titanium alloy

    CN116228648A